Cyanobacterial Hydrogen Metabolism : Regulation and Maturation of Hydrogenases - Devine, Ellenor (Uppsala universitet, Mikrobiell kemi, 2011)
In times with elevated CO2 levels and global warming there is a need of finding alternatives to carbon based energy carriers. One such environmental friendly solution could be H2 produced by living organisms. Cyanobacteria are good candidates since they can produce H2 from sunlight and water through the combination of photosynthesis and H2 producing enzymes i.e. nitrogenases and/or [NiFe]-hydrogenases. This thesis investigates the maturation and transcriptional regulation of [NiFe]-hydrogenases in cyanobacteria, with a special focus on hydrogenase specific proteases. The core of all hydrogenases consists of the small and large subunit. The large subunit in which the catalytic site is located goes through an extenstive maturation process which ends with a proteolytic cleavage performed by a hydrogenase specific protease (HupW/HoxW). This thesis shows that within the maturation process of hydrogenases, the proteolytic cleavage is probably the only step that is specific with respect to different types of hydrogenases i.e. one type of protease cleaves only one type of hydrogenase. Further in-silico analysis revealed that these proteases and the hydrogenases might have co-evolved since ancient time and that the specificity observed could be the result of a conserved amino acid sequence which differs between the two types of proteases (HupW/HoxW). A number of different transcription factors were revealed and shown to interact with the promoter regions of several of the genes encoding maturation proteins. The results indicate that the hydrogenase specific proteases are regulated on a transcriptional level in a similar manner as the hydrogenases they cleave. This thesis contributes with knowledge concerning transcriptional regulation and protein regulation of hydrogenases which will be useful for designing genetically engineered cyanobacteria with an improved and adjustable H2 production. === Felaktigt tryckt som Digital Comprehensive Summaries of Uppsala Dissertations from the Faculty of Science and Technology 722